PENGARUH BRAND TRUST DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA RUMAH SAKIT SAMARINDA MEDIKA CITRA DI SAMARINDA - Anisa Mulyasa Insani; Tetra Hidayati; Saida Zainurossalamia (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Anisa Mulyasa Insani, The Effect of Brand Trust and Customer Experience on Customer Satisfaction and Customer Loyalty at Samarinda Medika Citra Hospital in Samarinda. Supervised by Mrs Dr. Tetra Hidayati, SE., M.Si and Mrs. Dr. Saida Zainnurossalamia, SE., M.Si. The purpose of this study was to find out about Â The Effect of Brand Trust and Customer Experience on Customer Satisfaction and Customer Loyalty at Samarinda Medika Citra Hospital in Samarinda. This research is a quantitative research. The population in this study is the entire community in the city of Samarinda and have used services at the Samarinda Medika Citra hospital. The sample used in this study amounted to 90 respondents and using accidental sampling technique. The data analysis technique used is path analysis. In this study, the data used are primary and secondary data. The primary data collection method is carried out by a survey method with a questionnaire that distributed directly using Google Form, the primary data processing in this study used SPSS version 20 assistance program. The results of this study indicate that : (1) The relationship of Brand Trust has a positive and significant influence on Customer Satisfaction (2) Customer Experience has a positive and significant influence on Customer Satisfaction (3) Customer Satisfaction has a positive and significant influence on Customer Loyalty (4) Brand Trust has a positive and significant influence significant to Customer Loyalty (5) Customer Experience has a positive and significant influence on Customer Loyalty.